Neurological Complications of Anderson-Fabry Disease - Tuttolomondo, Antonino; Pecoraro, Rosaria; Simonetta, Irene; Miceli, Salvatore; Arnao, Valentina; Licata, Giuseppe; Pinto, Antonio (Current Pharmaceutical Design, 2013)
Characteristic clinical manifestations of AFD such as acroparesthesias, angiokeratoma, corneal opacity, hypo/ and anhidrosis, gastrointestinal symptoms, renal and cardiac dysfunctions can occur in male and female patients, although heterozygous females with AFD usually seem to be less severely affected. The most prominent CNS manifestations consist of cerebrovascular events such as transient ischaemic attacks (TIAs) and (recurrent) strokes. For the most part, CNS complications in AFD have been attributed to cerebral vasculopathy, including anatomical abnormalities. The natural history of Fabry patients includes transitory cerebral ischaemia and strokes, even in very young persons of both genders. The mechanism is partly due to vascular endothelial accumulation of Gb-3. White matter lesions (WML) on occur MRI. Both males and females can be safely treated with enzyme replacement; and thus screening for Fabry disease of young stroke populations should be considered. There are, however, no hard data of treatment effect on mortality and morbidity. Stroke in Anderson-Fabry disease study of 721 patients with cryptogenic stroke, aged 18–55 years, showed a high prevalence of Fabry disease in this group: 5% (21/432) of men and 3% (7/289) of women. Combining results of both sexes showed that 4% of young patients with stroke of previously unknown cause had Fabry disease, corresponding to about 1-2% of the general population of young stroke patients. Cerebral micro- and macro-vasculopathy have been described in Fabry disease. Neuronal globotriaosylceramide accumulation in selective cortical and brain stem areas including the hippocampus has been reported by autopsy studies in FD, but clinical surrogates as well as the clinical relevance of these findings have not been investigated so far. Another Neurologic hallmark of Fabry disease (FD) includes small fiber neuropathy as well as cerebral micro- and macroangiopathy with premature stroke. Cranial MRI shows progressive white matter lesions (WML) at an early age, increased signal intensity in the pulvinar, and tortuosity and dilatation of the larger vessels. Conventional MRI shows a progressive load of white matter lesions (WMLs) due to cerebral vasculopathy in the course of FD. Another study has been conducted to quantify brain structural changes in clinically affected male and female patients with FD. The peripheral neuropathy in Fabry disease manifests as neuropathic pain, reduced cold and warm sensation and possibly gastrointestinal disturbances. Patients with Fabry disease begin having pain towards the end of the first decade of life or during puberty. Children as young as 6 years of age have complained of pain often associated with febrile illnesses with reduced heat and exercise tolerance. The patients describe the pain as burning that is often associated with deep ache or paresthesiae. Some patients also have joint pain. A high proportion of patients with Fabry disease is at increased risk of developing neuropsychiatric symptoms, such as depression and neuropsychological deficits. Due to both somatic and psychological impairment, health-related quality of life (QoL) is considerably reduced in patients with Fabry disease. Targeted screening for Fabry disease among young individuals with stroke seems to disclose unrecognized cases and may therefore very well be recommended as routine in the future. Furthermore, ischemic stroke is related to inflammation and arterial stiffness and no study had addressed this relationship in patients with AF disease and cerebrovascular disease, so this topic could represent a possible future research line.
Keywords: stroke